PRIBUMI SUBALTERN DALAM NOVEL-NOVEL INDONESIA PASCAKOLONIAL - Iswadi Bahardur, S.S., M.Pd. (Universitas PGRI Sumatera Barat, 2017)
This research is motivated by colonial problems in the archipelago that still leave traces of oppression as well as efforts of the struggle of the natives to escape from the impact of the ideology. The trail of colonial colonization that still lags behind creates indigenous groups that become subalterns-isolated, oppressed, and discarded groups. In the postcolonial theory of subaltern Gayatri Spivax it is stated that among the most victimized groups of colonialism are women. Relevant to the issue, this study aims to describe the forms of oppression and the struggle of indigenous people, especially women who become subalterns, against the colonial ideology. Data obtained from modern Indonesian novels are then analyzed qualitatively. Based on the research data source, Orang-orang Blanti by Wisran Hadi, Maya by Ayu Utami and Gadis Pantai by Pramoedya Ananta Toer, the result of this research shows that indigenous figures, especially women become subaltern because they are marginalized, economically impoverished, labeled, As well as experiencing sexual harassment. Furthermore the form of the struggle of indigenous women in the face of colonial oppression in the context of the subaltern is to foster the spirit of struggle by recalling the glory of the past, practicing the knowledge gained through modern education, maintaining traditional and cultural values, as well as mimicryKeywords: novel, women, postcolonial, indigenous, subaltern